Instrumental Variables: An Econometrician's Perspective - Guido W. Imbens (Institute for the Study of Labor (IZA), 2014)
I review recent work in the statistics literature on instrumental variables methods from an econometrics perspective. I discuss some of the older, economic, applications including supply and demand models and relate them to the recent applications in settings of randomized experiments with noncompliance. I discuss the assumptions underlying instrumental variables methods and in what settings these may be plausible. By providing context to the current applications a better understanding of the applicability of these methods may arise.
Keywords: C01; 330; simultaneous equations models; randomized experiments; potential outcomes; noncompliance; selection models; instrumental variables